Agreement and Discrepancy on Emotional and Behavioral Problems Between Caregivers and HIV-Infected Children and Adolescents From Uganda - van den Heuvel, Leigh L.; Levin, Jonathan; Mpango, Richard S.; Gadow, Kenneth D.; Patel, Vikram; Nachega, Jean B.; Seedat, Soraya; Kinyanda, Eugene (Frontiers in Psychiatry, 2019)
Background: HIV infected children and adolescents (CA-HIV) face significant mental health challenges related to a broad range of biological and psychosocial factors. Data are scarce on the agreement and discrepancy between caregivers and CA-HIV regarding emotional and behavioral problems (EBPs) in CA-HIV. Objectives: We determined agreement between self- versus caregiver-reported EBPs and describe factors associated with informant discrepancy among caregiver-youth dyads who participated in the ‘Mental health among HIV infected CHildren and Adolescents in KAmpala and Masaka, Uganda’ (CHAKA) study. Methods: In a cross-sectional sample, caregiver-reported EBPs were assessed with the Child and Adolescent Symptom Inventory-5 (CASI-5) and self-reported problems were evaluated with the Youth Inventory-4 (YI-4) in 469 adolescents aged 12-17 years and the Child Inventory-4 (CI-4) in 493 children aged 8-11 years. Adolescents were questioned about experiences of HIV stigma and caregiver psychological distress was assessed with the Self-Reporting Questionnaire (SRQ-20). Linear regression models were applied to identify variables associated with discrepancy scores. Results: Self-reported emotional problems (EPs) were present in 28.8% of adolescents and 36.9% of children and 14.5% of adolescents self-reported behavioral problems (BPs). There was only modest correlation (r ≤ 0.29) between caregiver and CA-HIV reported EBPs, with caregivers reporting more EPs whereas adolescents reported more BPs. Informant discrepancy between adolescents and caregivers for BPs was associated with adolescent age and caregiver’s employment and HIV status. Among adolescents, EP discrepancy scores were associated with adolescent’s WHO HIV clinical stage, caregiver level of education, and caregivers caring for other children. Among children, EP discrepancy scores were associated with child and caregiver age, caregiver level of education, and caregiver self-rated health status. HIV stigma and caregiver psychological distress were also associated with discrepancy, such that adolescents who experienced HIV stigma rated their EPs as more severe than their caregivers did and caregivers with increased psychological distress rated EBPs as more severe than CA-HIV self-rated. Conclusions: EBPs are frequently endorsed by CA-HIV and agreement between informants is modest. Informant discrepancy is related to unique psychosocial and HIV-related factors. Multi-informant reports enhance the evaluation of CA-HIV and informant discrepancies can provide additional insights regarding the mental health of CA-HIV.